NANOEMULSIONS FOR PROSTRATE CANCER THERAPY: AN OVERVIEW - P, Manikandan; R, Sundara Ganapathy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The objective of this review is to focus the inferences of low/poor bioavailability and lack of dose proportionality for the oral delivery of drugs in prostate cancer therapy. To overcome such problems, various formulation strategies has been reported including various methods for the use of surfactants, cyclodextrins, solid dispersions, micronization, permeation enhancers, and lipids. Flutamide is an antiandrogen drug and used for the therapy of prostate cancer. The flutamide drug is having limited clinical application due to its poor water solubility and needs enhancement of its dissolution rate in simulated gastric fluids. The lipid-based formulations such as nanoemulsion have been shown to improve the solubility and oral absorption of lipophilic drugs. To conclude, this article emphasizes the various approaches of nanoemulsion based formulation for prostate cancer therapy. Â